How does primary debulking surgery compared to neoadjuvant chemotherapy followed by interval debulking surgery affect overall survival in women with advanced ovarian cancer? : A Systematic Review - Amanda Ezra Natasya Napitupulu; Jenary Immanuel Surbakti (The International Journal of Medical Science and Health Research, 2026)
Introduction: Advanced epithelial ovarian cancer (stage III-IV) remains a leading cause of gynecologic cancer mortality worldwide. The optimal initial treatment approach—primary debulking surgery (PDS) versus neoadjuvant chemotherapy followed by interval debulking surgery (NACT-IDS)—continues to generate substantial clinical debate despite multiple randomized trials. This systematic review aims to compare overall survival outcomes between PDS and NACT-IDS in women with advanced ovarian cancer. Methods: A systematic review was conducted following PRISMA guidelines. We screened studies based on predefined criteria: inclusion of women ≥18 years with FIGO stage III-IV epithelial ovarian cancer, direct comparison of PDS versus NACT-IDS, reporting of overall survival outcomes, and study designs including randomized controlled trials, cohort studies, systematic reviews, and meta-analyses. Data extraction encompassed study characteristics, patient selection criteria, treatment details, survival outcomes, surgical outcomes, and subgroup analyses. Results: Eighty studies were included, comprising five major RCTs (EORTC 55971, CHORUS, SCORPION, JCOG0602, TRUST) and numerous meta-analyses and observational studies. Meta-analyses demonstrated no significant difference in overall survival between PDS and NACT-IDS (HR 0.96, 95% CI 0.86-1.08) [1-3]. Individual RCTs confirmed similar findings: EORTC 55971 (HR 0.98, 90% CI 0.84-1.13) [4], CHORUS (HR 0.87, 95% CI 0.72-1.05) [5], and TRUST (HR 0.89, 95% CI 0.74-1.08) [6]. However, NACT-IDS achieved superior complete cytoreduction rates (RR 2.34, 95% CI 1.48-3.71) [2] with significantly lower perioperative mortality (RR 0.16, 95% CI 0.06-0.46) and major complications (RR 0.22, 95% CI 0.13-0.38) [1]. Observational studies consistently favored PDS, reflecting selection bias [7,8]. Stage-specific analysis revealed NACT-IDS benefited stage IV disease (HR 0.76, 95% CI 0.58-1.00) [9], while PDS showed advantage in stage III with limited metastatic burden [6,8]. Discussion: The apparent contradiction between RCT and observational evidence reflects fundamental differences in patient selection, surgical quality, and study design. Complete cytoreduction at PDS identifies a biologically favorable subset with superior outcomes, whereas achieving complete resection after NACT may indicate chemotherapy responsiveness without equivalent survival benefit. NACT-IDS offers clear perioperative safety advantages, making it preferable for unresectable disease, poor performance status, and extensive stage IV disease. Optimal treatment selection requires accurate preoperative assessment of resectability, patient fitness, and surgical expertise. Conclusion: PDS and NACT-IDS provide comparable overall survival in advanced ovarian cancer when patients are appropriately selected. PDS remains preferred when complete cytoreduction is achievable by experienced surgeons in fit patients with stage IIIC disease. NACT-IDS is a safe, effective alternative for patients with unresectable disease, poor fitness, or extensive stage IV disease. Future research should focus on validated prediction models incorporating clinical, imaging, and molecular markers to optimize individualized treatment selection.